Vitreous Analysis in the Management of Uveitis - Erika M. Damato; Martina Angi; Mario R. Romano; Francesco Semeraro; Ciro Costagliola (Mediators of Inflammation)
A correct diagnosis of uveitis is often challenging, given the wide range of possible underlying conditions and the lack of typical phenotypes. Management decisions may be difficult in view of the risk of visual loss with either inappropriate or delayed therapy. Analysis of the vitreous may therefore be used to provide the clinician with valuable information. In this paper, we describe the main clinical situations in which vitreous sampling is indicated and provide some guidance to clinicians for tailoring their requests. These situations include suspected intraocular infection and suspected intraocular malignancy. We describe the principal tests carried out on vitreous samples, including cultures, polymerase chain reaction-based testing, and cytokine analysis. Limitations of the tests used are likely to become less as more advanced testing methods are introduced. The importance of selecting the appropriate investigations to support a clinical suspicion is emphasised, as is the interpretation of test results within a clinical context.